Hadrah and Islamic Da’wah as Instruments of Socio-Religious Transformation: A Case Study of Youth and Local Culture in Sumbek Hamlet, Muncan Village - Anam, Khaerul; Suprapto, Suprapto; Faizah, Faizah (AS-SABIQUN, 2025)
This study investigates the role of hadrah as a medium of socio-religious transformation, a topic that remains underexplored despite its profound impact on youth character formation and communal identity in rural Islamic settings. Focusing on Sumbek Hamlet, Muncan Village, the research aims to understand how participation in hadrah fosters social, religious, and moral development among youth. Utilizing a qualitative research design, the study engaged 25 purposively selected participants, including youth members, religious instructors, community leaders, parents, and local officials. Data were collected through interviews, observations, and documentation, then analyzed thematically to uncover key dimensions of transformation. The findings reveal that hadrah functions as a dynamic space for both social and spiritual learning. Socially, it promotes discipline, cooperation, and group solidarity through collective rehearsals and performances that reinforce a shared identity. Religiously, it deepens spiritual awareness and moral internalization through devotional lyrics, rhythmic dzikr, and communal acts of worship. The study concludes that hadrah operates as a living medium of cultural da’wah, blending artistic expression with religious devotion to create a transformative ecosystem of faith and community engagement. Theoretically, the study contributes to Cultural Transformation Theory and Religious Socialization Theory by illustrating how traditional religious arts function as vehicles for value transmission and identity formation. Practically, it offers insights for educators, religious leaders, and policymakers to harness hadrah as an informal yet effective pedagogical tool for character education and spiritual development. Future research is recommended to explore hadrah’s transformative potential in urban and gender-diverse contexts.